The Mediating Role of Employee Factor in the Relationship between Sensory Marketing and Economic Performance of Ghana’s Foodservice Sector - Nanekum, Isaac; Solomon, Abekah Keelson (Technium Social Sciences Journal, 2022)
In today’s business environment, establishing a positive business climate is becoming increasingly important for organisational performance. A positive employee factor creates a social atmosphere, which encourages high employee involvement and an employee-centered culture. In response, employees feel comfortable and contribute positively to financial performance of the business. Given the intensity of competition in the service industry, firms must understand how the employee factor affect their performance. This study examined the way the employee factor mediates the relationship between sensory marketing and organisational performance in the Foodservice Sector of Ghana. The study used quantitative research method for data collection through survey questionnaires. The questionnaires were developed and distributed directly in physical form at the restaurants through stratified sampling method. The study used a total of 38 management staff and 331 customers as respondents for the data collection. The research data was analysed through Structural Equation Modelling (SEM) and Analysis of Moment of Structures (AMOS), with the support of the maximum likelihood estimator to achieve the covariance of the constructs. The mediating variable was measure by the binary outcome variable with Andrew Hayes Process Model. The results indicate that sensory marketing has a significant positive relationship on economic performance. In addition, no mediating effect was found in the relationship between sensory marketing and economic performance. Cross-sectional data, a restricted target sample senior staff of restaurants, and a restricted target area (i.e. Greater Accra Region) were limitations of this study. In addition, the dimensions of economic performance were identified as market share, profitability and sales growth. Finally, the hypothesised relationship was explored only for the foodservice sector. Therefore, the results of this study will assist foodservice operators to develop and implement market-orientated strategies to help achieve sales growth, enhance profit, and market share among themselves. It is hoped this study will be a useful reference point for future academic researchers who will undertake similar study in relation to the discussed variables.